Ensino de notas musicais ao piano para um menino com Autismo - Langendonck, Melanie Fairlie Pearson Van (Universidade Federal de São Carlos, 2019)
Children with Autism Spectrum Disorder (ASD) may present deficits in communication and social interaction, as well as restricted and repetitive behaviors and interests. Research has been carried out in the area of music, however the majority of studies for this population contemplate the use of music as a therapeutic and not an educational activity. Were found studies that evaluated the teaching of rudimentary reading of musical notes through stimulus equivalence and mostly with individuals with typical development. This study had as a general objective to verify the effects of conditional discriminations between figures (each composed of a background color and a specific musical symbol) and keys in the recognition of musical notes to the piano in a boy with 4 years and 10 months of age diagnosed with ASD. As specific objectives, verify if the control of the answer would be given by the color or symbol of the musical figures, examine the formation of classes of equivalent stimuli and test the recombination of the notes learned in new musical sequences. The method had an experimental design with multiple baseline between sets of musical notes. The teaching, which had procedures of the Applied Behavior Analysis (ABA), was divided in three phases, in which seven musical notes written in the treble clef, from central C to central B, were taught in configurations that ranged from one to 38 combined and recombined symbols (units). A pre and post-test were applied at all phases. The connection between symbol and color cards and the corresponding keys (AB) and between cards with symbol and color and the name of the corresponding note (AD) were taught. The procedure of teaching discrimination of musical notes promoted the acquisition of repertoire referring to musical reading, as measured by the response of playing the corresponding key. The results suggest efficacy in teaching with an achievement of over 70% in the teaching and testing phases. Emerging relations between teaching classes could also be noticed. It is intended with this research, expand previous studies found In music and equivalence with adults for a child with ASD.
Teaching piano musical notes to a boy with Autism
Keywords: Educação especial; Transtorno do espectro do autismo; Equivalência de estímulos; Leitura musical; Special education; Autism Spectrum Disorder; Stimulus equivalence; Musical reading.; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM